Epistemological beliefs of secondary school teachers about digital competencies training. A comparative analysis between Spain, Mexico and Colombia - Banoy, Wilder (2026)
Training in Digital Competence for Teachers (FCDD) is often based on assessments that focus solely on the level of digital competence. However, this approach overlooks a crucial component of curriculum design: teachers' epistemological beliefs about their own training in this field. In response to this need, this research comparatively analyzes the level of sophistication of these beliefs among secondary school teachers and their curricular implications. A descriptive, quantitative, and analytical study was developed using a 20-item instrument based on the Schommer-Aikins model. The sample included 94 active teachers from the public sector in Valencia (Spain), Yucatán (Mexico), and Zipaquirá (Colombia). Descriptive analysis by subcategories, one-way ANOVA, and Scheffé's post hoc test were applied. The results show significant differences in knowledge stability, allowing us to reject the null hypothesis for that specific case. Mexico and Colombia do not differ from each other, while Spain differs from both. In terms of training, sophisticated beliefs favor the integration of emerging technologies and the design of innovative pedagogical strategies; they also strengthen curriculum planning linked to FCDD. A training approach is required that explicitly recognizes these beliefs in order to adjust curriculum designs to the real context, reduce fragmented views of FCDD, and mitigate resistance associated with less dynamic conceptions of knowledge.